'Incidental' ethnographers : French Catholic missions on the Tonkin-Yunnan frontier, 1880-1930 - Michaud, Jean, 1957- (Studies in Christian mission,, 2007)
This book, connecting the fields of social anthropology and missiology, presents a body of colonial ethnographic writing applied to highland societies in the southern portion of the Mainland Southeast Asian massif. The writers under scrutiny are Catholic priests from the Société des Missions Étrangères de Paris. Their texts from the Upper-Tonkin vicariate, in today's northern Vietnam, are paid special attention, notably through its major contributor, F.M. Savina. The author locates this ethnographic heritage against its historical, political and intellectual background. A comparison is conducted with French missionaries-cum-ethnographers who worked among the 'natives' in New France (Canada) in the 17th century, yielding the unexpected conclusion that practically nothing from this early period of experimentation was remembered.